2014
DOI: 10.1111/bph.12582
|View full text |Cite
|
Sign up to set email alerts
|

The TRPM4 channel inhibitor 9‐phenanthrol

Abstract: The phenanthrene-derivative 9-phenanthrol is a recently identified inhibitor of the transient receptor potential melastatin (TRPM) 4 channel, a Ca 2+ -activated non-selective cation channel whose mechanism of action remains to be determined. Subsequent studies performed on other ion channels confirm the specificity of the drug for TRPM4. In addition, 9-phenanthrol modulates a variety of physiological processes through TRPM4 current inhibition and thus exerts beneficial effects in several pathological condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 79 publications
8
91
0
Order By: Relevance
“…9-Phenanthrol specifically targets TRPM4 channels and has been used in a variety of biological preparations to reveal the contribution of these channels in physiological processes (18). The results from the current study suggest a critical role for the TRPM4 channels in human DSM excitability and contractility.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…9-Phenanthrol specifically targets TRPM4 channels and has been used in a variety of biological preparations to reveal the contribution of these channels in physiological processes (18). The results from the current study suggest a critical role for the TRPM4 channels in human DSM excitability and contractility.…”
mentioning
confidence: 59%
“…This agent has been successfully used to study TRPM4 channel activity in various preparations (18), including rodent DSM (39,44,45). However, recent studies indicated that 9-phenanthrol inhibits transmembrane protein 16A (TMEM16A) channels (5) in vascular smooth muscle and activates intermediate-conductance Ca 2ϩ -activated K ϩ (IK) channels (12) in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, 9-phenanthrol was identified as a selective TRPM4 blocker [7], with an IC 50 of 20 µM in transfected HEK293 cells and an IC 50 of 1 µM in endothelial cells [8, 9]. …”
Section: Introductionmentioning
confidence: 99%